Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4103/0019-5413.106910
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of posterior tibial slope with metaphysiodiaphyseal angle in total knee arthroplasty: A radiological study

Abstract: Background:Posterior tibial slope (PTS) is an important factor affecting postoperative range of motion (ROM) following total knee arthroplasty (TKA). Metaphysio-diaphyseal angle (MDA) is a new entity defined as angle between proximal anatomical axis and metaphyseal axis of tibia. This study was undertaken to determine PTS in Indian patients and find its correlation with MDA of tibia. Accuracy of extramedullary jigs and the influence of MDA on the accuracy was also evaluated. This study is a retrospective analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The authors 11 evaluated 133 knees using preoperative CT for patients undergoing total knee arthroplasty (TKA) for osteoarthritis and concluded that PTS measurements were deeply influenced by degenerative changes. Mohanty et al 23 evaluated the PTS value in a cohort of 100 Indian patients undergoing TKA. The global PTS was 11.6° (range, 2°-25°).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors 11 evaluated 133 knees using preoperative CT for patients undergoing total knee arthroplasty (TKA) for osteoarthritis and concluded that PTS measurements were deeply influenced by degenerative changes. Mohanty et al 23 evaluated the PTS value in a cohort of 100 Indian patients undergoing TKA. The global PTS was 11.6° (range, 2°-25°).…”
Section: Discussionmentioning
confidence: 99%
“…Methods of estimating the PTS are controversial and not consistent. The long anatomic axis of the tibia was used in our study, 3,37 as in the studies of Kuwano et al 17 and Mohanty et al 23 However, Weinberg et al 32 took for reference the center of the first third of the tibial shaft, and Han et al 11 published results with 4 different axes: mechanical axis, anatomic axis, anterior cortices, and fibular shaft axis. Yoo et al 35 highlighted the wide difference of the PTS according to the chosen axis: anterior cortices (13.8°), proximal anatomic axis (10.8°), central anatomic axis (12.9°), posterior cortices (7.8°), and fibular shaft (9.5°).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the offset in the mediolateral direction, an increased anteroposterior offset may further bring the tibial keel in proximity with the posterior cortex. The tibial intramedullary canal is located anterior to the center of the tibial plateau in Asian compared to Caucasian [2,3]. Furthermore, Asians tend to have an increased posterior slope angle as compared to Caucasians, which further increases the risk of posterior cortex impingement [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the size of the tibia in Taiwanese people is relatively smaller than that in Caucasians; hence, smaller sized components are more frequently used. In addition, the Asian population has different tibial intramedullary canal features and proximal tibia morphology compared to Caucasians [2][3][4][5][6]. We, therefore, conducted this study to identify the risk factors for posterior cortex injury associated with AA-sized tibial implants and potential measures for the prevention of complications.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 PTS is steeper in the patients who has osteoarthritis of knee. 12 Tibial plateau slopes, MTS and LTS, independently are important determinants of knee biomechanics. 2,[13][14][15] Steeper medial tibial plateau slope, lateral tibial plateau slope and shallower medial tibial plateau depth has also been recognized as a risk factors for anterior cruciate ligament injury.…”
Section: Introductionmentioning
confidence: 99%